PERSONAL DATA MISUSE IN FINTECH LENDING PROVIDERS FROM PERSPECTIVE INDONESIAN CYBERLAW - Rahmawati, Elvia; Huda, Miftakhul; Aldhi, Ian Firstian (Airlangga Development Journal, 2024)
This study aims to investigate the forms of personal data misuse by fintech lending providers and the legal measures that can be taken when such misuse occurs, within the context of Indonesian cyber law. The background of this research is driven by the rapid development of fintech lending, which is often exploited for criminal activities, including personal data misuse. The method used is normative legal research with statutory and conceptual approaches. The results show that personal data misuse by fintech lending providers can take various forms, such as unauthorized data usage, illegal disclosure of personal information, and the use of malware to access data. Such violations can result in criminal penalties under Law No. 27 of 2022 on Personal Data Protection. The conclusion is that there is a need for stricter supervision of fintech lending providers and increased public awareness of personal data protection. Recommendations include the implementation of stricter regulations by the Financial Services Authority (OJK), more intensive supervision by the Indonesian Fintech Association, and public education on their rights regarding personal data.